O problema de Cauchy para sistemas quase-lineares hiperbólicos é bem posto em espaços de Hölder - Silva, Rômel da Rosa da (2012)
We consider the Cauchy problem for the quasi-linear systems that is, the system is hyperbolic at u = 0. We show that certain Besov spaces are preserved by flow of the solution, near the null solution.